FOOD AND BEVERAGE CONTROL IN SELECTED 2-5 STAR HOTELS IN NAIROBI, KENYA. - Gesage, Bichage M. (IJRDO - Journal of Applied Management Science, 2017)
The purpose of the study was to determine the types of cost control measures operational in2 – 5 star hotels and establish if these measures were effective in keeping the cost of saleswithin acceptable limits. The study was carried in 2-5 star hotels within Nairobi province. Ninehotels were studied.Measures of independence including Chi-square tests were used to highlight whethersignificant associations between were different variables. Analysis of variance was performedto test if there were significant differences between the actual and standard food and beveragecost.The results revealed that there were significant differences between actual and standardbeverage costs amongst all the star hotel categories. There were equally significant differencesbetween the actual and standard/target food cost targets. The mean standard beverage costsbetween the various hotel star categories were significant at 95% confidence level.Higher star rated hotels were more likely to meet their food and beverage costs than their lowerrated counterparts because there was a significant association between the hotel star categoryand the likelihood of meeting the food and beverage cost targets. Higher rated hotels did nothave a serious costs side problem and could make more profits by giving more attention to thedemand side, by encouraging more people to consume their services. Lower ranked hotelsappeared to have cost side problems. Therefore more profits can be realized by these hotels ifthey institute more stringent cost control measures.